Early in vivo target genes in human immune cells highlight vitamin D’s role in antioxidant defense - Tripathi, Tanya; Carlberg, Carsten (Frontiers in Immunology, 2025)
IntroductionVitamin D plays a vital role in modulating innate and adaptive immunity. This study investigated the gene regulatory mechanisms underlying this modulation in vivo.MethodsWe conducted a proof-of-principle intervention in which a participant received a bolus of vitamin D3 (80,000 IU) monthly for three months. Peripheral blood mononuclear cells (PBMCs) were collected immediately before and at 4, 24, and 48 hours post-supplementation for transcriptome-wide differential gene expression analysis.ResultsWe identified 570 genes significantly responsive to vitamin D3 (p < 0.05) at one or more timepoints. In vitro experiments using PBMCs of the 0-hour time point of the same individual validated 303 of these as targets of the vitamin D receptor ligand 1α,25-dihydroxyvitamin D3. Among these, 55 primary target genes exhibited significant changes as early as 4 hours post-supplementation, including genes like SELENOS (selenoprotein S), which plays a key role in the selenium micronutrient network. Moreover, genes such as PRDX1 (peroxiredoxin 1), TXNRD1 (thioredoxin reductase 1), and SOD2 (superoxide dismutase 2), involved in antioxidant defense, were prominently regulated.DiscussionThese findings highlight a potential early and primary role for vitamin D in regulating detoxification processes, suggesting its critical involvement in maintaining redox homeostasis in immune cells of healthy individuals.